2020
DOI: 10.1038/s41598-020-68441-0
|View full text |Cite|
|
Sign up to set email alerts
|

High-throughput screening reveals higher synergistic effect of MEK inhibitor combinations in colon cancer spheroids

Abstract: Drug combinations have been proposed to combat drug resistance, but putative treatments are challenged by low bench-to-bed translational efficiency. To explore the effect of cell culture format and readout methods on identification of synergistic drug combinations in vitro, we studied response to 21 clinically relevant drug combinations in standard planar (2D) layouts and physiologically more relevant spheroid (3D) cultures of HCT-116, HT-29 and SW-620 cells. By assessing changes in viability, confluency and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(47 citation statements)
references
References 47 publications
(72 reference statements)
5
36
1
Order By: Relevance
“…We demonstrated that the in vitro response in cells growing in monolayer does not always reflect the situation in more complex systems. The strong differential activity of olaparib in 3D vs. 2D growing cells was particularly intriguing, and was not in agreement with the finding obtained with other cellular systems and other drugs [ 34 , 35 , 36 , 37 , 38 ]. Olaparib, a drug currently under investigation in different solid tumors [ 39 , 40 , 41 , 42 , 43 ], is a potential candidate for MPM due to the reported mutations in the BRCA1-associated protein (BAP-1) gene found in MPM.…”
Section: Discussioncontrasting
confidence: 68%
“…We demonstrated that the in vitro response in cells growing in monolayer does not always reflect the situation in more complex systems. The strong differential activity of olaparib in 3D vs. 2D growing cells was particularly intriguing, and was not in agreement with the finding obtained with other cellular systems and other drugs [ 34 , 35 , 36 , 37 , 38 ]. Olaparib, a drug currently under investigation in different solid tumors [ 39 , 40 , 41 , 42 , 43 ], is a potential candidate for MPM due to the reported mutations in the BRCA1-associated protein (BAP-1) gene found in MPM.…”
Section: Discussioncontrasting
confidence: 68%
“…The type of compound interaction was determined by calculating the Bliss predicted value for independent effect (E AB,Bliss ) and Bliss excess ( b ) followed by a t-test using a method described elsewhere ( Folkesson et al, 2020 ) with some modifications. The effect of each treatment was evaluated calculating the fractional inhibition (FI) when compared to the inoculum control.…”
Section: Methodsmentioning
confidence: 99%
“…The type of compound interaction was determined by calculating the Bliss predicted value for independent effect (E AB,Bliss ) and Bliss excess ( b ) followed by a t-test using a method described elsewhere (Folkesson et al, 2020) with some modifications (See Supplementary Material and Methods ). Pairwise combinations with b ≥ 0.08, 0.08 ≤ b ≥ −0.08 and b ≤ −0.08 were classified as synergistic, additive and antagonistic, respectively, when the p -value was ≤ 0.05.…”
Section: Methodsmentioning
confidence: 99%
“…The type of compound interaction was determined by calculating the Bliss predicted value for independent effect (EAB,Bliss) and Bliss excess (b) followed by a t-test using a method described elsewhere (Folkesson et al, 2020) with some modifications. The effect of each treatment was evaluated calculating the fractional inhibition (FI) when compared to the inoculum control.…”
Section: Compound Interaction Assaymentioning
confidence: 99%